Characterization of tachykinin NK2 receptor in the anterior pituitary gland - Pisera, Daniel Alberto (2003)
Tachykinins are a family of bioactive peptides that interact with three subtypes of receptors: NK1, NK2 and NK3. Substance P has greater affinity for NK1, and neurokinin A (NKA) for NK2 receptor subtype. Although only NK1 receptor has been characterized in the anterior pituitary gland, some evidence suggests the existence of NK2 receptors in this gland. Therefore, we investigated the presence of NK2 receptors in the anterior pituitary gland of male rats by radioligand binding studies using labeled SR48968, a non peptidic specific antagonist. [3H]SR48968 specific binding to cultured anterior pituitary cells was time-dependent and saturable, but with a lower affinity than previously reported values for cells expressing NK2 receptors. Unlabeled NKA inhibited only partially [3H]SR48968 specific binding to whole anterior pituitary cells. Since SR48968 is a non polar molecule, we performed experiments to discriminate surface from intracellular binding sites. SR48968 exhibited both surface and intracellular specific binding. Analysis of the surface-bound ligand indicated that [3H]SR48968 binds to one class of receptor with high affinity. Neurokinin A completely displaced [ 3H]SR48968 surface specific binding fitting to a two-site/two-state model with high and low affinity. Additionally, immunocytochemical studies showed that the NK2 receptor is expressed at least in a subset of lactotropes. These results demonstrate the presence of NK2 receptors in the anterior pituitary gland and suggest that NKA actions in this gland are mediated, at least in part, by the NK2 receptor subtype.